PROFILES OF SENSITIZATION TOWARDS THE ALLERGENS OF BIRCH POLLEN IN CHILDREN WITH POLLINOSIS LIVING IN THE RUSSIAN MIDLAND - M. A. Snovskaya; A. A. Ananyina; O. V. Kojevnikova; L. S. Namazova-Baranova (Union of pediatricians of Russia, 2015)
.